ANALISIS PENGELOLAAN KEUANGAN DESA BERDASARKAN PERATURAN MENTERI DALAM NEGERI NOMOR 20 TAHUN 2018 - Ratno A. Entengo; Julie Abdullah; Hasanuddin; Deby R. Karundeng (Jurnal Visionida, 2023)
The purpose of this study was to determine the suitability of village financial management in one of the sub-districts, North Gorontalo Regency based on Permendagri number 20 of 2018. The research method used is a qualitative method. The data analysis used in this research is qualitative with an interactive analysis model consisting of three components of analysis namely: 1) Data reduction; 2) Presentation Data; 3) Data Verification and Conclusion Drawing. The results of the study show that with village financial analysis based on Permendagri Number 20 of 2018 through (a) Planning Aspects are in accordance with Permendagri but there are still deficiencies in apparatus that have not complied with the provisions and the impact is delays in the planning process (b) Implementation Aspects are in accordance with Permendagri and the weakness is the understanding of the apparatus that is still lacking, causing delays in the implementation process, (c) For the Administrative aspect it is considered good because it is in accordance with the instructions and technical requirements requested (d) The Reporting Aspect is considered good but the drawback is the slowness of the apparatus on duty late in providing reporting to the North Gorontao Regency government, and (e) The aspect regarding the coverage response is considered good because it has been adjusted to the instructions and technical requirements required by the regulation of the minister of home affairs in financial accountability.